RPA Demystified: How Software Robots are Revolutionizing Customer Service - Mayank Choubey, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Robotic Process Automation (RPA) is revolutionizing customer service by introducing software robots capable of handling repetitive tasks with unprecedented efficiency and accuracy. This article explores the transformative impact of RPA on customer service operations, drawing parallels with everyday automation experiences to demystify the technology. Through case studies and empirical evidence, we examine how RPA streamlines processes such as data entry, ticket routing, and customer data retrieval, leading to significant improvements in operational efficiency and customer satisfaction. The article addresses common misconceptions about RPA, emphasizing its role as a complement to human workers rather than a replacement. We analyze the synergy between RPA and human customer service representatives, highlighting increased employee productivity and job satisfaction. The article also delves into the future prospects of RPA in customer service, including emerging trends like cognitive RPA, while discussing potential obstacles to widespread adoption and strategies for successful implementation. By presenting a comprehensive overview of RPA's capabilities, benefits, and challenges in the customer service domain, this article provides valuable insights for organizations seeking to enhance their customer service operations through automation.
Keywords: Robotic Process Automation; Customer Service Automation; Digital Workforce Integration; Operational Efficiency; Cognitive RPA